Studi Literatur: Peningkatan Keterampilan Kolaborasi Siswa dalam Pembelajaran IPAS Melalui Model Team Games Tournament (TGT) - Qoirina, Nabila Sabha; Hidayah, Ratna (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Collaborative skills play a crucial role in preparing students to face the challenges of 21st-century education, particularly in the IPAS (Science and Social Studies Integration) subject at the elementary school level. This study aims to review the literature on the Team Games Tournament (TGT) model to improve students' collaborative skills. The study employs a qualitative method with a systematic literature review approach, drawing from various academic sources published between 2020 and 2025, including journals, books, and previous relevant studies. A total of four scientific articles were selected using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method to identify appropriate sources. The subjects of this study are students who demonstrate low levels of collaborative skills. The review findings indicate that the TGT model is effective in creating a collaborative learning environment, enabling students to actively contribute, work productively with others, take responsibility, show flexibility and willingness to compromise, and communicate effectively. Therefore, the Team Games Tournament (TGT) model is recommended as an educational innovation in IPAS learning to enhance collaborative skills among elementary school students.Keterampilan kolaborasi berperan penting dalam membekali siswa untuk menghadapi tantangan pendidikan di abad 21, khususnya dalam mata pelajaran IPAS di Sekolah Dasar. Tujuan penelitian ini adalah mengkaji literatur tentang Model Team Games Tournament (TGT) untuk meningkatkan keterampilan kolaborasi siswa. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi literatur (systematic literature review) dari berbagai sumber akademik rentang tahun 2020-2025 seperti jurnal, buku, dan hasil penelitian sebelumnya sejumlah empat artikel ilmiah dengan yang menggunakan proses pengumpulan data PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analysis) untuk mendapatkan jurnal yang dibutuhkan. Subjek kajian ini yaitu peserta didik yang masih rendah untuk keterampilan kolaborasi. Hasil kajian menunjukkan model Team Games Tournament (TGT) terbukti efektif dalam menciptakan suasana belajar kolaboratif yang mampu memfasilitasi siswa untuk berkontribusi secara aktif, bekerja sama secara produktif, sikap tanggung jawab, fleksibel dan kompromi serta omunikasi. Dengan demikian, model Team Games Tournament (TGT) dapat direkomendasikan sebagai inovasi pembelajaran IPAS untuk peningkatan keterampilan kolaboratif pada siswa sekolah dasar.